PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN IKLIM ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR DI PERUSAHAAN DENGAN KEPUASAN KERJA SEBAGAI MEDIATING VARIABLE (STUDI KASUS: PT EVI) - Pia Asrunputri, Aisyah; Supriyadi, Edy; Putriana, Lies (SEKOLAH PASCASARJANA PRESS, 2020)
The purpose of this study was to determine the effect of leadership style, organizational culture, and organizational climate on organizational citizenship behaviour (OCB) which was mediated by job satisfaction and to prove the hypothesis regarding the relationship of research variables: leadership style, organizational culture, organizational climate, job satisfaction, and organizational citizenship behaviour. The population of this study is all employees in marketing department of PT EVI and employs 212 employees. The statistical method used in this study is Structural Equation Modelling (SEM), which was operated through the LISREL Program. This study showed that leadership style was the strongest predictor and has the biggest influence on organizational citizenship behaviour, which was mediated by job satisfaction